The Urgency of Law Enforcement in the Case of Personal Data Leakage in Indonesia - Khuan, Hendri; Diharjo, Nugroho Noto (Ipso Jure, 2025)
This study discusses the weak law enforcement in the case of personal data leakage in Indonesia, even though normatively there has been recognition of data protection rights through Law No. 27 of 2022 concerning Personal Data Protection (PDP Law). The phenomenon of data leaks involving various sectors, including major cases such as BPJS Kesehatan, reflects the ineffectiveness of previous regulations and the suboptimal implementation of the PDP Law. The lack of a Personal Data Protection Authority (OPDP) has also exacerbated the disorder in handling data leaks which is often not transparent and unaccountable. This study uses a normative approach with doctrinal analysis of positive legal regulations and Islamic legal principles, especially related to the individual's right to privacy. The findings show that there is a serious gap between the law in the books and the law in action. The absence of a strong legal precedent, weak awareness of the authorities, and lack of coordination between institutions, cause violations of the right to privacy to often not be adequately acted upon. Therefore, systemic legal reforms, the establishment of independent supervisory bodies, and a progressive and evidence-based approach to law enforcement are needed, so that the protection of personal data truly functions as an instrument of social justice and human rights protection in the digital era.